ANALISIS RELIABILITY KOMPONEN STASIUN PENGISIAN KENDARAAN LISTRIK UMUM (SPKLU) DENGAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Setiawan, Falih; Haryadi , Gunawan Dwi; Prahasto, Toni; Widodo , Achmad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Air pollution remains a critical issue that requires prompt and effective resolution. One of the primary strategies to mitigate this problem is the promotion of electric vehicle (EV) usage. However, several challenges persist, including high initial investment costs, inadequate charging infrastructure, and long charging durations. This study aims to analyze the reliability of Public Electric Vehicle Charging Stations (SPKLU) using the Failure Mode and Effect Analysis (FMEA) method. The strength of the FMEA approach lies in its ability to identify potential failure risks, prioritize corrective actions based on the Risk Priority Number (RPN), and provide recommendations for improving the reliability of SPKLU systems. This method enables the reduction of system downtime and maintenance costs. The results reveal that major causes of SPKLU system failures include short circuits, overheating, and inadequate maintenance. The reliability values obtained were 67.36% for the charging sub-system, 36.78% for the control sub-system, and 50% for the overall system. This research offers practical contributions to the development of more reliable and sustainable electric vehicle infrastructure.